Hydroisomerization of n-dodecane on ZSM-48 with acid distribution modulation for high diffusion performance - Wei Zhang; Jiangnan Xiang; Yuting Wang; Mengxi Ma; Yan Wang; Bo Qin; Weijiong Dai; Binbin Fan; Jiajun Zheng; Ruifeng Li (Fuel Processing Technology)
In this paper, a one-dimensional ten-membered ring microporous molecular sieve ZSM-48 is employed as a model catalyst, with the number and positional distribution of acid sites in ZSM-48 molecular sieve adjusted by regulating the temperature of templating agent exfoliation. XRD, FT-IR, SEM, TG, NH3-TPD, N2 adsorption-desorption, and the zero-length column (ZLC) method are used for characterization and analysis. The decrease in the distribution depth of acid sites within the microporous channels of ZSM-48 will not only significantly affects the hydroisomerization performance of n-dodecane (resulting in a final yield of isododecane of more than 80 %) but also influences the yield ratio of multi-branched and mono-branched isomers. After the conversion is stabilized, the yield ratio of multi-branched to mono-branched isomers for Z-48-350 is 1.4 to 2.1 times higher than that for Z-48-550. Furthermore, acid site distribution depth profoundly influences reactant diffusion, with Z-48-120 exhibiting a 115 % higher effective diffusion constant than Z-48-550 at 140 °C. Shortening the distribution depth of acid sites in the micropores does not significantly change the product distribution of n-dodecane monomethyl isomers but markedly suppresses the cracking reaction due to reduced diffusion limitation of olefinic intermediates. This enables efficient and selective hydroisomerization of long-chain n-alkanes.